RELEVANCE OF ADAPTING THE BEST PRACTICES APPLIED IN THE USA IN THE PROCESS OF CONCEPTUALIZING THE VETERANS POLICY IN UKRAINE: A HISTORICAL ANALYSIS - Mariia BAZAIEVA (Association of Social and Educational Innovation, 2024)
This article reveals the relevance and possibilities of adopting the best practices of the United States in Ukraine in the process of conceptualizing the model of the state veterans policy's development. It provides historical analysis of the process of conceptualizing the updated models of veterans policy in the United States and Ukraine, with its key milestones highlighted. Major components of the latest model of the veterans policy have been defined, with the process of its development in the United States analyzed. The historical stages of conceptualizing the state veterans policy in the United States and Ukraine have been consistently studied, with milestone historical events and factors that had impact on its development in each of the countries defined. The findings of the research make us conclude that the United States have demonstrated a long-lasting evolutionary process of developing the concept of the latest model of the veterans policy. First of all, this concept offering a wide variety of veterans support programs is comprehensive and integrative; being human-centered, it is focused on the process of adapting former military personnel to civilian life. But in Ukraine, the veterans policy's development started only in the last decade. We make conclusions about the relevance of adopting the essential elements of the concept of the veterans policy's latest model at the state level in Ukraine in the context of the full-scale invasion of the Russian Federation. This makes it necessary to further study in detail the expertise of the United States and carry out comparative historical analysis of the processes of conceptualizing the state veterans policy in Ukraine and the United States in order to identify ways to effectively adapt the American best practices in the process of conceptualizing the veterans policy in Ukraine.